Kualitas Silase dengan Penambahan Molasses dan Suplemen Organik Cair (Soc) di Desa Sukamju, Kecamatan Cikeusal - Titin Patimah; Asroh Asroh; Kumala Intansari; Nanda Delvia Meisani; Rendi Irawan; Afton Atabany (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
Silage making activities were held on July 9, 2020 in the farm area owned by one of the agriculture office's target in Sukamaju Village, Cikeusal District, Serang Regency. The purpose of this activity is as a solution to feed shortages in the dry season and excess feed in the rainy season. In addition to knowing the advantages of silage feed compared to the usual forage and knowing the characteristics of good silage so as not to occur poisoning. The composition of the ingredients used in the manufacture of silage is 70% odot grass, 30% roomy grass, liquid organic supplement (SOC) 5 cc, molasses 15 cc and water 1 liter with anaerobic fermentation process. The good quality of silage can be known from the color, aroma, texture and presence of mushrooms. Good silage is brownish green, acidic, textured crumbs and no mushrooms. Silage is also an alternative feed that has a stable content of carbohydrates, proteins and vitamins. Keywords : silage, fermentation, quality, anaerob fermentation